Activity-dependent neuroprotective protein (ADNP) is an alcohol-responsive gene and negative regulator of alcohol consumption in female mice - Ziv, Yarden (Neuropsychopharmacology, 2018)
Neuroadaptations in the brain reward system caused by excessive alcohol intake, lead to drinking escalation and alcohol use disorder phenotypes. Activity-dependent neuroprotective protein (ADNP) is crucial for brain development, and is implicated in neural plasticity in adulthood. Here, we discovered that alcohol exposure regulates Adnp expression in the mesolimbic system, and that Adnp keeps alcohol drinking in moderation, in a sex-dependent manner. Specifically, Sub-chronic alcohol treatment (2.5 g/kg/day for 7 days) increased Adnp mRNA levels in the dorsal hippocampus in both sexes, and in the nucleus accumbens of female mice, 24 h after the last alcohol injection. Long-term voluntary consumption of excessive alcohol quantities (~10–15 g/kg/24 h, 5 weeks) increased Adnp mRNA in the hippocampus of male mice immediately after an alcohol-drinking session, but the level returned to baseline after 24 h of withdrawal. In contrast, excessive alcohol consumption in females led to long-lasting reduction in hippocampal Adnp expression. We further tested the regulatory role of Adnp in alcohol consumption, using the Adnp haploinsufficient mouse model. We found that Adnp haploinsufficient female mice showed higher alcohol consumption and preference, compared to Adnp intact females, whereas no genotype difference was observed in males. Importantly, daily intranasal administration of the ADNP-snippet drug candidate NAP normalized alcohol consumption in Adnp haploinsufficient females. Finally, female Adnp haploinsufficient mice showed a sharp increase in alcohol intake after abstinence, suggesting that Adnp protects against relapse in females. The current data suggest that ADNP is a potential novel biomarker and negative regulator of alcohol-drinking behaviors.